2018
DOI: 10.1186/s12978-018-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Early initiations of first antenatal care visit and associated factor among mothers who gave birth in the last six months preceding birth in Bahir Dar Zuria Woreda North West Ethiopia

Abstract: BackgroundTiming of Antenatal care booking is one of the basic components of antenatal care services; that helps to early detection, managing, and prevention of problems during the pregnancy and helps the mother to receive full packages of antenatal care services. However, in the world including Ethiopia, significant numbers of pregnant mothers were not booking the follow up on the recommended time. The main aim of this study was to assess the prevalence and factors that associated with the early timing of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 17 publications
20
69
2
Order By: Relevance
“…In Sub Saharan Africa, it was indicated that early antenatal care contacts' coverage was less than 50% in 2013 and has the highest maternal mortality ratio (MMR) of 546 per 100,000 live births in 2015) [4]. The same study found out that, less than half 46.8% of the pregnant women sought early antenatal care.…”
Section: Background Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…In Sub Saharan Africa, it was indicated that early antenatal care contacts' coverage was less than 50% in 2013 and has the highest maternal mortality ratio (MMR) of 546 per 100,000 live births in 2015) [4]. The same study found out that, less than half 46.8% of the pregnant women sought early antenatal care.…”
Section: Background Of the Studymentioning
confidence: 98%
“…During antenatal care booking, assessments and tests are conducted on pregnant women, which include measuring of blood pressure to exclude pregnancy induced hypertension, urine testing to exclude proteinuria and weight monitoring to establish intrauterine growth restriction department of health [4]. Immunization against various infectious diseases such as tetanus, Human Immune virus (HIV) testing and counseling of pregnant women and if she tests positive, she will be initiated on antiretroviral therapy (ART) for elimination of mother-to-child transmission of HIV [5].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Majority of these deaths occur among pregnant women who did not receive ANC. [1][2][3][4][5] Despite good progress in access and utilization of ANC visits globally, studies have shown that only 17% of women ever received any ANC and the proportion of women who are receiving the recommended focused ANC minimum of four visits still low. [6][7][8] Timely antenatal care is the period in which pregnant women visited ANC at less than four months of pregnancy, while late antenatal care is the period in which women start attending ANC at greater than or equal to four months of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…ANC can provide an opportunity to promote the bene t of skilled attendance at birth and health facility based delivery. During ANC visits women are counseled about the bene t of institutional delivery, risk of home delivery, birth preparedness and complication readiness that can promote women to deliver at health facility with the help of skilled birth attendants [42][43][44]. This implies that ANC is an intervention that a pregnant woman receives from organized health care services.…”
Section: Factors Associated With Institutional Delivery Service Utilimentioning
confidence: 99%